Edukasi Pemberian Kudapan Berbasis Pangan Lokal Guna Meningkatkan Pemahaman Asupan Gizi Anak Di Desa Mentor - Rifqi Aji Saputra; Binti Azizatun Nafi’ah; Lisa Dwi Yuliana; Aristyana Vira Anggraini; Khoirotun Annisah (Jurnal Pengabdian kepada Masyarakat Nusantara, 2023)
Education on providing local food-based snacks can help prevent stunting rates from increasing. Stunting occurs when toddlers do not get enough nutrition so that it affects the child's growth. This activity aims to educate parents about the importance of nutritional intake for toddlers through local food-based snacks. The target of this activity is 20 mothers and toddlers in the Mentor Village who are recorded as experiencing stunting. The method used in this activity is Service Learning (SL). The results show that: 1) Parents already have knowledge about nutritional composition and menu variations, 2) Parents know the type and amount of food that is appropriate for the age of the toddler, 3) Parents understand how to process food so that the nutrients can be absorbed by the toddler's body, 4) Parents know the child's diet and the importance of regular meal times, 5) Parents realize the importance of supervising and accompanying food intake to ensure that toddlers get adequate nutrition.